Fifteen novel microsatellite loci, developed using next-generation sequencing, reveal the lack of genetic structure in Donax vittatus from Iberian Peninsula. (5th February 2019) - Fernández-Pérez, Jenyfer; Nantón, Ana; Arias-Pérez, Alberto; Insua, Ana; Méndez, Josefina
Abstract: The wedge clam Donax trunculus is an important shellfish species in several southern European countries. Nevertheless, production of this species has suffered a sharp decrease, especially in Galicia (Northwest of Spain). In the face of the collapse of a fishery, while the object species recovers, a suitable strategy is the exploitation of a similar species, and Donax vittatus could potentially be an alternative exploitable resource. Such exploitation should be carried under appropriate management practises to avoid transferring the problem to the new species. Given the need to reveal the population structure and to elucidate appropriate management units of D. vittatus along the Atlantic coast of the Iberian Peninsula, fifteen variable microsatellite markers were reported and tested in seven localities (six of them previously studied with a mitochondrial COI marker). All localities displayed similar genetic diversity values (allelic richness: 10.75–15.20; expected heterozygosity: 0.813–0.845; and expected heterozygosity: 0.389–0.460). Significant deficits of heterozygotes were recorded for all populations, probably due to null alleles. Analyses of population differentiation, including global F ST, pairwise F ST with and without null allele correction, number of migrants and Analyses of Molecular Variance, indicated lack of genetic structure in D. vittatus along Atlantic coast of the Iberian Peninsula, confirming the previous results based on COI gene. These data are useful to assist the fishery development and the conservation plans of this species. Furthermore, the panel of developed microsatellites will allow further genetic population studies throughout the geographic distribution of the species, as well as other genetic analysis needed for aquaculture activities.